PENURUNAN ANGKA KUMAN SEBELUM DAN SESUDAH BERKUMUR DENGAN POVIDONE IODINE - Lestari, Diah; Ananda, Liandry Dea Dwi; Setiawan, Heru; Prasetyorini, Tri (jitek, 2024)
Povidone-iodine is considered to have the broadest spectrum of antimicrobial action compared with other common antiseptics. Based on the application protocol of commercial Povidone Iodine (PVP-I) mouthwash to support a healthy lifestyle, PVP-I is commonly used in concentrations of 1.0% with a contact time of 30 seconds. The higher the concentration of antiseptic, the smaller the time needed to kill microbes, but the maximum limit of concentration and contact time needs to be considered to minimize the toxicity effects to remain safe, effective, and efficient. This study aims to determine the comparison of germ numbers before and after gargling with povidone-iodine mouthwash based on variations in the concentration of 0.2%, 0.4%, 0.6%, 0.8%, and 1% with variations in contact time of 15 and 30 seconds. The method of this research was an actual experiment with a pre-post-test design. Based on the Non-Parametric Friedman test with a confidence level of 95% (α = 0,05), there is a significant difference between the germs number before and after gargling with PVP-I in every variation of concentration and contact time (p-value = 0.00). This study concludes that PVP-I 0.2% concentration variation with 15 seconds of contact time has been effective in decreasing the number of germs.